2006
DOI: 10.1088/0268-1242/21/6/013
|View full text |Cite
|
Sign up to set email alerts
|

A complex Fourier transformation study of the contactless electroreflectance of an undoped-n+GaAs structure

Abstract: Complex Fourier transformation (CFT) has been employed to analyse contactless electroreflectance (CER) spectra from an undoped-n + GaAs structure with various ac modulations and dc bias voltages. The CFT spectra of CER have been compared with those of photoreflectance (PR). It has been found that the CER non-flat modulation is between the built-in electric field and a larger electric field which increases with the modulation voltage. The result has been explained by the screening of the applied modulation elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The relative error for ˜( ) H z A slightly improved to 48% versus 61% at h -= 1 for q G =  0.01 , as shown in figure 1(b). Contrastingly, the relative error for ˜( ) H z [60,61] in the analysis of FKOs. In future, the impact of previous errors on the PR spectra transition into low-field regime as it approaches the third-derivative regime may be investigated.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The relative error for ˜( ) H z A slightly improved to 48% versus 61% at h -= 1 for q G =  0.01 , as shown in figure 1(b). Contrastingly, the relative error for ˜( ) H z [60,61] in the analysis of FKOs. In future, the impact of previous errors on the PR spectra transition into low-field regime as it approaches the third-derivative regime may be investigated.…”
mentioning
confidence: 93%
“…around eight FKO peaks away from the CP. Equation (15) and its region of validity had been fundamental for graphical techniques [57][58][59] and fast Fourier transforms [60,61] in the analysis of FKOs; hence, an assessment of its accuracy is essential. Figure 1(a) depicts the relative error (RE) for ˜( ) H z A in the dotted red line for Lorentzian broadening q G =  0.01 within FKO's moderate-field regime.…”
mentioning
confidence: 99%
“…In 1991, Yin and Pollak 16 have proposed a new contacless mode of electroreflectance spectroscopy which utilizes a capacitor‐like system. This technique usually is called as contactless electroreflectance (CER) spectroscopy and is successfully applied by several groups 17–24. In this paper, the application of CER spectroscopy to study nitride structures (bulk crystals, epitaxial layers, heterojunction structures, and QWs) is presented and following issues are discussed: (i) the surface band bending in ammonothermal GaN (A‐GaN) crystals of various types of conductivity and GaN epilayers doped by Si and Mg; (ii) the built‐in electric field in AlGaN/GaN heterojunction structures; and (iii) the Stokes shift in InGaN/GaN multi QWs (MQWs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kudrawiec et al [5] showed that oscillation features below the GaAs bandgap usually observed in PR spectra of n-type GaAsbased structures could be eliminated in CER measurements. More recently, a comparison study on CER and PR for an undoped-n + (UN + , also referred to as surface-intrinsic-n + [6]) GaAs structure has been performed by the authors [7]. It is found that CER and PR cannot give identical line shapes of Franz-Keldysh oscillations (FKOs).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy is essentially attributed to different modulation mechanisms of CER and PR, though modulated reflectance signals for both the methods are produced by the modulation to the built-in electric field. In the case of CER, the asymmetric carrier dynamics of return to thermodynamical equilibrium under the modulation field (fast screening of the forward modulation voltage, and very slow screening of the reverse one because of the electron trapping on the surface states) results in the modulation between the built-in electric field and a larger field [7]. For PR, however, modulation is achieved by photovoltage induced by the pump laser and is between the built-in field and a reduced field.…”
Section: Introductionmentioning
confidence: 99%